A Study of the Determinants of Corporate Social Responsibility Disclosure: Evidence from China - Yu, Jin (2020)
The aim of this dissertation is to analyse whether stakeholder power and several corporate characteristics are potential determinants of corporate social responsibility disclosure (CSRD) practices in China. Stakeholder power consists of shareholders, government, and creditor power, and corporate characteristics include firm size, industry classification, and profitability. To achieve the objective described above, the quantitative method was adopted. The significance of these explanatory variables was tested by employing the data of listed firms involved in the SSE corporate governance index group in 2017 and 2018, which were collected from the database and the website of Rankings Corporate Social Responsibility Rating (RKS). This study provides evidence that firms with higher CSRD ratings are found to show statistically significant higher leverage and profitability, and be more likely to belong to state-owned enterprises and high-profile industries. Nevertheless, shareholder power and firm size seem to be unable to explain the CSRD in China.